A new approach for reliability-centered maintenance programs in electric power distribution systems based on a multiobjective genetic algorithm - Piasson, Diego; Bíscaro, André A.P.; Leão, Fábio B. [UNESP]; Mantovani, Roberto S. [UNESP] (Elsevier, 2016)
This paper proposes a multiobjective model to solve the mathematical problem of optimizing reliability-centered maintenance planning of an electric power distribution system (EPDS). The main goal is to minimize the preventive maintenance costs while maximizing the index of reliability of the whole system. In the proposed model, the limits of the indices, such as SAIDI and SAIFI, are considered as constraints of the maintenance programs. The reliability indices of the EPDS components are evaluated and updated by a fuzzy inference system. A NSGA-II algorithm was proposed to solve the multiobjective model that provides an optimized Pareto frontier. The results obtained from applying the proposed methodology to a system with three feeders and 733 components are presented, showing its robustness and quality for maintenance planning in EPDS.
Keywords: Fuzzy systems; NSGA-II; Power quality; Power system reliability; Preventive maintenance; Reliability centered maintenance